Critical stress for an infinitely long flat plate with elastically restrained edges under combined shear and direct stress - Stowell, Elbridge Z. (National Advisory Committee for Aeronautics, 1943)
A simple interaction curve is presented for evaluating the conditions of combined shear and direct stress under which an infinitely long, flat plate with equal elastic restraints against rotation along the edges will become unstable. The theoretical work that led to the interaction curve is presented in the form of appendixes.
NACA Wartime Report L-340.
Originally issued as NACA as Advance Restricted Report L3K13 (November 1943).
Prepared at the Langley Memorial Aeronautical Laboratory, Langley Field, Virginia.
Keywords: Plates (Engineering); Shear (Mechanics); Buckling (Mechanics); Loads (Mechanics); Strains and stresses.; Charts, diagrams, etc.; elektronické knihy; electronic books